Gender and mechanization: exploring the sustainability of mechanized forage chopping in Tanzania - Fischer, Gundula; Wittich, S.; Malima, G.; Sikumba, Gregory N.; Lukuyu, Ben A.; Ngunga, D.; Rugalabam, J. (Elsevier, 2018)
Mechanization is currently experiencing a revival in agricultural research and development, with a new emphasis on equity and sustainability. This study evaluates the introduction of forage chopper machines in seven villages in northern Tanzania from a farmer's perspective. Data collected through focus group discussions and a survey are used for a gender analysis of this technology within a broader sustainable intensification indicator framework. The results not only draw attention to unabated challenges to smallholder mechanization (such as high operational costs or weak supporting infrastructures), but also show how the technology's sustainability is contingent upon equity dynamics on the household and community levels. The evaluation framework proved suitable for a holistic assessment. A broader approach to gender issues would strengthen its interdisciplinary claim. Suggestions for promoting the chopper's sustainability include gender-sensitive training and the establishment of group models for machine operation based on agreed and fair regulations.